2016
DOI: 10.1089/aid.2015.0273
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sequencing Analysis of Human T Cell Lymphotropic Virus Type 1 Long Terminal Repeat 5′ Region from Patients with Tropical Spastic Paraparesis/Human T Cell Lymphotropic Virus Type 1-Associated Myelopathy and Asymptomatic Carriers

Abstract: The aim of this study was to analyze patients by deep sequencing the human T cell lymphotropic virus type 1 (HTLV-1) long terminal repeat (LTR) region in order to determine if minor and/or major mutations in this promoter region might be associated with tropical spastic paraparesis (TSP)/human T cell lymphotropic virus type 1-associated myelopathy (HAM) outcome or proviral load or HTLV-1 expression. This study is a cross-sectional analyze of 29 HTLV-1-infected patients with TSP/HAM or asymptomatic carriers. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Of the 59 articles that used the Sanger method , 56 reported partial genome sequences, and three reported complete sequencing of the HTLV-1 genome. Of the four articles that used NGS [12,75,78,79], two reported partial genome sequences and two reported complete genome sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 59 articles that used the Sanger method , 56 reported partial genome sequences, and three reported complete sequencing of the HTLV-1 genome. Of the four articles that used NGS [12,75,78,79], two reported partial genome sequences and two reported complete genome sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Using next-generation sequencing, Rego et al . [48] have shown that HTLV-1-carriers with low PVL had increased frequency of proviruses containing minor polymorphic mutations in TRE-II, Ets-2, Sp1 and E-box sequences within the 5′ LTR compared to individuals with high PVL. In our study, all HTLV-1 provirus sequences had conserved Ets-1/2 and Sp1-binding sites, TATA box, and poly(A) signal.…”
Section: Discussionmentioning
confidence: 99%